Material Evidence of the Early Christian Occupation in the Great Temple of Amun-Ra at Karnak - Durand, Benjamin (Near Eastern archaeology, 2019)
Since 2008, the sector of the Temple of Ptah at Karnak has been subject to an epigraphic, architectural, and archaeological survey (fig. 1). It offers a tremendous opportunity for a diachronic study of the history of occupation in the domain of Amun (Thiers and Zignani 2013). Remains found by Guillaume Charloux in 2015 allow for a closer look at the first occupation of the sector dating back to the Middle Kingdom (Charloux 2017). Likewise, surface structures abandoned at the end of the fourth or middle of the fifth century CE (David 2013, 2017) provide a unique opportunity to gather information about this less-studied period of the area. While in-depth excavation has allowed for a limited peek at the earlier occupation, the surface remains have been cleared and documented in a much more extensive way despite being subjected to long-term human and climatic interference. As a result, all Byzantine remains were excavated as part of the multidisciplinary program conducted in the sector of the Temple of Ptah. The broad extent of the excavation allows for a comprehensive picture, meaning not only a better understanding of the spatial organization of the structures, but also of their function (at least for some of them). Furthermore, the examination of the objects discovered has allowed for the study of the local community and its culture.